2023
DOI: 10.3390/rs15164085
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionality Reduction and Anomaly Detection Based on Kittler’s Taxonomy: Analyzing Water Bodies in Two Dimensional Spaces

Giovanna Carreira Marinho,
Wilson Estécio Marcílio Júnior,
Mauricio Araujo Dias
et al.

Abstract: Dimensionality reduction is one of the most used transformations of data and plays a critical role in maintaining meaningful properties while transforming data from high- to low-dimensional spaces. Previous studies, e.g., on image analysis, comparing data from these two spaces have found that, generally, any study related to anomaly detection can achieve the same or similar results when applied to both dimensional spaces. However, there have been no studies that compare differences in these spaces related to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 35 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…Our research is applied in this context. Among all pertinent areas of research, we found our inspiration to solve this matter in remote sensing and studies related to Kittler's Taxonomy, such as [11,16,17]. This study opens up a range of possibilities for future work in remote sensing and other areas.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Our research is applied in this context. Among all pertinent areas of research, we found our inspiration to solve this matter in remote sensing and studies related to Kittler's Taxonomy, such as [11,16,17]. This study opens up a range of possibilities for future work in remote sensing and other areas.…”
Section: Introductionmentioning
confidence: 87%
“…Lastly, by adding the two results obtained in the multiplication step, the final result was created. This step is expressed by Equations ( 15)- (17).…”
Section: Image Editingmentioning
confidence: 99%
See 3 more Smart Citations